Dissolved organic matter (DOM) in the open Mediterranean Sea. II: Basin–wide distribution and drivers of fluorescent DOM. (January 2019) - Martínez–Pérez, Alba María; Catalá, Teresa S.; Nieto–Cid, Mar; Otero, Jaime; Álvarez, Marta; Emelianov, Mikhail; Reche, Isabel; Álvarez–Salgado, Xosé Antón; Arístegui, Javier
Highlights: Peaks A, C and M distributions in epipelagic waters are mainly explained by AOU and temperature. Peaks E and T distributions in epipelagic waters are mainly explained by PHA. Water mass mixing explains FDOM distribution in meso– and bathypelagic waters. Abstract: Fluorescent dissolved organic matter (FDOM) in the Mediterranean Sea was analysed by excitation–emission matrix (EEM) spectroscopy and parallel factor (PARAFAC) analysis during the cruise HOTMIX 2014. A 4–component model, including 3 humic–like and 1 protein–like compounds, was obtained. To decipher the environmental factors that dictate the distributions of these components, we run generalized additive models (GAMs) in the epipelagic layer and an optimum multiparametric (OMP) water masses analysis in the meso– and bathypelagic layers. In the epipelagic layer, apparent oxygen utilization (AOU) and temperature presented the most significant effects on the variability of the marine humic-like peak M fluorescence, suggesting that its distribution was controlled by the net community respiration of organic matter and photobleaching. On the contrary, the variability of the soil humic-like peak E and the protein–like peak T fluorescence was explained mainly by the prokaryotic heterotrophic abundance, which decreased eastwards. In the meso– and bathypelagic layers, water mass mixing and basin–scale mineralization processes explained >72% and 63% of the humic–like and protein–like fluorescence variability, respectively. When analysing the two basins separately, the OMP model offered a better explanation of the distribution of fluorescence in the eastern Mediterranean Sea, as expected from the reduced biological activity in this ultra–oligotrophic basin. Furthermore, while western Mediterranean deep waters display the usual trend in the global ocean (increase of humic–like fluorescence and decrease of protein–like fluorescence with higher AOU values), the eastern Mediterranean deep waters presented an opposite trend. Different initial fluorescence intensities of the water masses that mix in the eastern basin, with Adriatic and Aegean origins, seem to be behind this contrasting pattern. The analysis of the transect–scale mineralization processes corroborate this hypothesis, suggesting a production of humic–like and a consumption of protein–like fluorescence in parallel with water mass ageing. Remarkably, the transect–scale variability of the chromophoric dissolved organic matter (CDOM) absorbing at the excitation wavelength of the humic–like peak M indicates an unexpected loss with increasing AOU, which suggests that the consumption of the non–fluorescent fraction of CDOM absorbing at that wavelength exceeded the production of the fluorescent fraction observed here.